Inside out, India and China local politics go global - Antholis, William (Brookings focus books, 2013)
For the last decade, China and India have grown at an amazing rate, particularly considering the greatest downturn in the U.S. and Europe since the Great Depression. As a result, both countries are forecast to have larger economies than the U.S. or EU in the years ahead. Still, in the last year, signs of a slowdown have hit these two giants. Which way will these giants go? And how will that affect the global economy? Any Western corporation, investor, or entrepreneur serious about competing internationally must understand what makes them tick. Unfortunately, many in the West still look at the two Asian giants as monoliths, closely controlled mainly by their national governments. Inside Out, India and China makes clear how and why this notion is outdated.